Morphological, phenological and pomological differentiation of commercial cultivars of blackberry (Rubus glaucus Benth) - Iza, Monica; Viteri, Pablo; Hinojosa, Milton; Martínez, Anibal; Sotomayor Correa, Andrea; Viera, William (Enfoque UTE, 2020)
The genus Rubus is one of the most diverse in terms of morphology and genetics, presenting a wide spectrum of wild and cultivated species that are desired by their edible fruits. In Ecuador, the cultivation of blackberry (R. glaucus and Rubus sp.) is present along the Inter-Andean region, grown between 2000 and 3100 masl. This fruit crop is economically important for its high demand for fresh and processed consumption. This research was carried out in the Tumbaco Experimental Farm of INIAP (Ecuador) with the objective of finding characters that allow the morphological, phenological and pomological differentiation of four blackberry cultivars (Castilla, Andimora, Colombiana and Brazos). The multivariate analysis showed three conglomerates (C). Cultivars Andimora and Colombiana (C3) do not have spines unlike Castilla (C2) and Brazos (C1). Colombian was the earliest cultivar (161 days of sprouting to harvest) and Castilla the latest (186 days). Brazos cultivar showed the highest fruit weight (5.85 g). Andimora reached the highest content of soluble solids (11.86 ºBrix) and had firm fruits. The differentiating characters observed in this study make possible to establish parameters of distinction between the cultivars that are currently cultivated in Ecuador.